Health Belief Model dan Management Hipertensi Pada Penderita Hipertensi Primer di Papua - Rayanti, Rosiana Eva; Nugroho, Kristiawan Prasetyo Agung; Marwa, Shendy Lusynthia (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: The prevalence of hypertension continus to increase. When suffering from hypertension, pattients must also carry out pressure management disease to control their blood. The Health Belief Model (HBM) can influence the pattientâ€™s health behavior.The purpuseof this research is to analyze the relationship between the Health Belief Model and Manegement Hypertension in primary hypertension sufferes in Papua.Diabetes Mellitus, Methods: This articleÂ use quantitative research with cross sectional design. The location of this research at Biak Kota Health Center, Papua from December 2019 until Ferbuary 2020. The criteria for respondents are hypertensive patients aged 20-55 years who were registered at the Biak Kota Health Center and the indigenous Biak Papua tribe. The instruments of research are the questionnaire Health Belief Model (about the level of confidence in the desease suffered) and hypertension management questionnaire (knowledge of the disease suffered and attitudes and actions taken). Patients also measured their blood pressure with a digital tension meter.Results:Â of data analysis with correlation test is no relationship between all indicators in the health belief model and hypertension management.Conclusion: there is a relationship between the actions with serious of perception, benefits, behavior, and confidence in the health belief model with a weak correlation.